PENGARUH JUMLAH CROSSLINKER PADA SINTESIS MOLECULARLY IMPRINTED POLYMER (MIP) TERHADAP KEMAMPUAN ADSORPSI KLORAMFENIKOL - Maria Monica Sianita; Magdalena Butar Butar (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2022)
This study aims to determine the effect of variations in the amount of crosslinker on the adsorption capability of Molecularly Imprinted Polymer (MIP)-Chloramphenicol (CAP) which was analyzed using the High-Performance Liquid Chromatography (HPLC) instrument and identify the –NO2 functional group in the polymer with the best variation in the amount of crosslinker using the instrument. Fourier Transform Infrared Spectroscopy (FTIR). In this study, MIP was synthesized using CAP as a template, ethylene glycol dimethacrylate (EGDMA) as a crosslinker, methacrylic acid (MAA) as a monomer, benzoyl peroxide (BPO) as an initiator, and acetonitrile as a porogen. The results showed that the variation in the number of crosslinkers affected the adsorption capability of MIP with the composition between CAP: MAA: EGDMA, namely 1:3:18, resulting in the largest adsorption capability of 2,2 mg/g with an extraction percentage of 66.11%. The results of functional group identification with FTIR showed that NIP contained –NO2 group at wave number 1524.27 cm-1 while in MIP no –NO2 group was detected because most of the CAP had been extracted, and PB was made as a control polymer without adding template CAP. Keywords: Chloramphenicol, Molecularly Imprinted Polymer, Crosslinker, Adsorption Capability